North Coast, Trinidad, B.W.I. - (:unkn) unknown (Unknown, 2011)
The postcard shows coconut palms along the coast in Trinidad.
Colour: Black and white; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Coasts--Trinidad and Tobago; Trees--Trinidad and Tobago; Coconut palm--Trinidad and Tobago; Seas--Trinidad and Tobago; Caribbean Sea; Bodies of water--Trinidad and Tobago; Scenic overlooks--Trinidad and Tobago; [1940]